영조 3년의 왕실사역에 참여한 각수 연구 - 김상호 (서지학연구, 0(72), 2017)
본 논문은 영조 3년에 『선원계보기략』을 간행할 때 순조롭게 진행되지 못한 교정청의 각수동원 문제를 분석하고, 그 당시 상황을 보다 정확히 이해하기 위해 같은 해에 진행된 두 가지 왕실사역, 즉 숙종실록의 간행 및 효장세자의 가례에 참여한 각수의 판각활동을 연구한 논문이다. 연구결과는 다음과 같다. 첫째, 『선원계보기략』에 대한 선행연구자가 미해결과제로 각수의 활동내용은 각수동원시점을 11월 3일이 아닌 10월 19일로 전제한 결과다. 둘째, 각수의 사역일자에 대한 교정청과 호조 간의 시비는 그 산정방식, 즉 일당제와 할당제의 차이에서 비롯된 것으로 보이며, 교정청이 호조에 요구한 요미와 각수에게 분급한 요미 간에 차이가 있는 것은 조각장의 동원과 관련이 있는 것으로 판단된다. 셋째, 『선원계보기략』은 당초 그 간행에 필요한 각수들을 대부분 북한산성의 각수로 충당할 계획이었으나, 사정이 여의치 않아 결국 교서관 각수 위주로 구성이 되었다. 넷째, 영조 3년에 벌어진 세 가지 왕실사역에 모두 참여한 각수는 유세흥으로 그는 당대의 대표적인 교서관 각수라 할 수 있는 김수해와 더불어 초기에 도자장으로 활동한 이력이 있다. 다섯째, 한업상은 훈련도감에 소속된 각수는 특히 석각과 옥각에 정통했고, 엄필득은 교서관과 어영청의 각수를 거쳐 금위영의 고자로 활동한 특이한 이력의 인물로 드러났다. This research focuses on activities of 17 engravers who participated in the three major Royal projects carried out during the 3rd year of King Yeongjo, namely printing of Sukjongsilrok, the auspicious ceremony of Prince Hyojang, and printing of Seonwongyebogiryak. It especially centers on the issue of recruiting engravers by Gyojeongcheong during the printing of Seonwongyebogiryak. The results are as follows. First, Yu Sehong, who joined all of the three projects, is notable as he worked as Dojajang in his early years with Kim Suhae, one of the most reputable engravers from Joseon Dynasty. Second, Han Eopsang was an engraver for Hunryeondogam, and was well-acquainted with stone and jade carving. Third, the unsolved problem on activities of engravers as suggested by preceding researcher related to Seonwongyebogiryak was based on the assumption that the recruitment was made on Oct. 19 instead of Nov. 3. Fourth, the differences in the calculation of working days and rice payment by Gyojeongcheong and Hojo resulted from the gap between daily-wage system and workload-quota system. The issue apparently resulted from jogakjeng’s recruitment problems. Fifth, the project for Seonwongyebogiryak was originally intended to be carried out with monk engravers of Bukhansanseong, but it was later changed to be conducted mainly by engravers of Gyoseogwan. KCI Citation Count: 0